THE OPTIMALIZATION OF LUBRICANT WASTE RECYCLING WITH LOW RANK COAL AS CONTAMINANT ABSORBANCE - Nining Sudini Ningrum; Ika Monika (Indonesian Mining Journal, 2005)
The research of lubricant waste recycling by means of low rank coal as absorbent is one of the ways to render efficient the oil consumption also to maximize the value of low rank coal. This research is a continuation research with a fixed variable, in which the amount of coal is increased to 20% from the amount of the lubricating oil and the heating time which took 2 hours was variated with the heating temperature variable from 150°C to 350°C, the size of coal granule –8+10, -12+14 and –20+24 mesh. The research output shows that the optimum temperature of the lubricating oil recycling by means of coal as absorbent is reached in the temperature of 300°C for the coal with the size –12+14 mesh. In this condition Ca content reduce from 1447 to 150 ppm, Zn reduce from 887 to 17,4 ppm, Fe reduce from 47,1 to 43,5 ppm, Ni reduce from 15,4 to 6,2 ppm and Cr and Cu are all absorbed. The coal resulted from the recycling process can be used as a direct fuel with the calorific value between 5000 to 6500 cal/g and the colour of the lubricating oil resulted from separation (base oil) is yellowish dark.